A comparison of reaction times of boys and girls aged 10-11 and 14-15 years - Brychta, Petr; Hojka, Vladimir; Heller, Jan; Konarski, Jan M.; Coufalova, Klara; Ruda, Tomas (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Pubescence is a life stage with the most turbulent progression of sensorimotor abilities during the transformation of a child into an adult. Differences in all sensorimotor abilities between boys and girls are become significant at this age. The progression of reaction abilities in girls decreases at this age (girls achieve peak values around the age of 15), while the reaction abilities in boys keep improving into adolescence. Younger children compared to adults and older children show a reduced ability to perform one or more tasks concurrently with a movement task. Aim of Study. The purpose of the study was to determine the time of complex reaction of the lower limbs of children. Moreover, a relationship between reaction time, age and gender was also found. Material and Methods. The research group included 81 primary school students aged 10-15 years. Subjects were divided into four groups according to age and gender (Group 1 – 9.8 to 10.8-yearoldgirls, n = 20; Group 2 – 10.0 to 10.7-year-old boys, n = 19; Group 3– 14.3 to 15.3-year-old girls, n = 21; and Group 4 – 14.2 to 15.2-year-oldboys, n = 21). The measurements were carried out using the FiTRO Agility Check test. A two-way ANOVA revealed statistically significant differences between the groups. The significance level was adjusted to0.05. Tukey’s post-hoc test was used to determine differences between pairs of groups. Results. There are significant differences between the boys and girls aged 14-15 years. Other differences between boys and girls aged 10-11 years were not statistically significant, however, girls performed with slightly shorter reaction times. Conclusions. The research showed a significant relationship between age and complex reaction speed in the age group of 14-15 of boys and girls. This study helps to prove that boys do not have shorter complex reaction times than girls aged 10-11 years.
Keywords: FiTRO Agility Check; complex reaction time; pubescence; age